2020
DOI: 10.1002/jimd.12298
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of multiple sulfatase deficiency: Retrospective phenotyping and functional variant analysis to characterize an ultra‐rare disease

Abstract: Multiple sulfatase deficiency (MSD) is an ultra-rare neurodegenerative disorder caused by pathogenic variants in SUMF1. This gene encodes formylglycine-generating enzyme (FGE), a protein required for sulfatase activation. The clinical course of MSD results from additive effect of each sulfatase deficiency, including metachromatic leukodystrophy (MLD), several mucopolysaccharidoses (MPS II, IIIA, IIID, IIIE, IVA, VI), chondrodysplasia punctata, and X-linked ichthyosis. While it is known that affected individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
85
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(89 citation statements)
references
References 22 publications
3
85
1
Order By: Relevance
“…For the assessment of language‐, swallowing‐ and gross motor function, standardized tools were used (expressive‐language‐function‐classification [ELFC‐MLD], 16 eating‐and‐drinking‐ability‐classification‐system [EDACS], 28 GMFC‐MLD, 17,18 gross‐motor‐function‐measure [GMFM‐88] 29 ) (Supplementary Material S1). Neurologic and somatic exam features and medical complications of MSD according to Adang et al 7 are shown in Supplementary Material S2. Long‐term disease course was followed up until the present (15 years, patient 1) or death (20 years, patient 2) by regular (non‐standardized) telephone contacts.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…For the assessment of language‐, swallowing‐ and gross motor function, standardized tools were used (expressive‐language‐function‐classification [ELFC‐MLD], 16 eating‐and‐drinking‐ability‐classification‐system [EDACS], 28 GMFC‐MLD, 17,18 gross‐motor‐function‐measure [GMFM‐88] 29 ) (Supplementary Material S1). Neurologic and somatic exam features and medical complications of MSD according to Adang et al 7 are shown in Supplementary Material S2. Long‐term disease course was followed up until the present (15 years, patient 1) or death (20 years, patient 2) by regular (non‐standardized) telephone contacts.…”
Section: Methodsmentioning
confidence: 99%
“…Confirmation of the identified SUMF1 variant in patient 1, diagnostic testing in patient 2, and carrier testing was done by Sanger sequencing. Genotype data and some clinical aspects of the two patients are published in a larger MSD cohort 7 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…I put a really big effort into encouraging enrolment in this study as did others (see Acknowledgements). I am delighted to say that robust natural history data on MSD has been published now 4 . Subsequently, some of the key authors of the care guidelines document and natural history study also extended their commitment to MSD research by writing a very important GeneReviews article on MSD which was also published 5 .…”
Section: Msd Research Efforts From My Perspectivementioning
confidence: 99%